Identification of Methicillin Resistance Staphylococcus aureus in Immunocompromised Host Using PCR Techinque and Detection of Its Sensitivity to Antibiotics (Journal of the College of Basic Education, 2022)
Two hundred and twenty clinical specimens were collected from were collected from patients in Medical City Hospitals (Baghdad /Iraq).During the period From November 2013 to April 2014.The specimens were included (54) ear swab, (56) blood, (70) burn swab, and (40) urine sample. It was found that (49.03%) of the 108 isolates were belong to Staphylococcus spp., were diagnosed as coagulase-positive staphylococci (COPS), where 112 (50.9%) of clinical samples were coagulase negative (CONS). From the collected clinical samples, 85(78.7%) were MRSA according to sensitivity test and vitek system, and the rest were MSSA 23(21.9%). In the present study, ceftaroline is drug of choice, because of it activity against Methicillin-resistant S. aureus .The effectiveness of the ceftaroline antibiotic are being tested on 85 isolate of Methicillin-resistant S. aureus (MRSA), all isolate were sensitive to ceftaroline.